Characteristics of Hypertensive Patients at Medan Johor Community Health Center: An Analysis Based on Age, Occupation, and Body Mass Index - Damanik, Rosa Zorayatamin; Rahmadhani, Mayasari (PT Inovasi Pratama Internasional, 2024)
According to the World Health Organization (WHO), approximately 1.13 billion people worldwide suffer from hypertension. In Indonesia alone in 2018, the prevalence of hypertension reached 34.1% in people over 18 years of age. Knowledge of the relationship between hypertension characteristics and the degree of hypertension in the Medan Johor area will help the community health center in the prevention and management of hypertension. This study used a cross-sectional design with hypertension patients who participated in the referral program at the Medan Johor health center. The data collection technique used secondary data in the form of medical record data at the Medan Johor health center. Data analysis was performed using chi-square analysis. The results showed that gender (p=0.131) and uric acid levels (p=0.182) did not have a significant relationship with the degree of hypertension. While age (p=0.008), occupation (p<0.001), body mass index (p=0.013), total cholesterol level (p<0.001) and blood sugar level (p=0.031) have a significant relationship with the degree of hypertension.